The effectiveness of unified transdiagnostic therapy on strategies cognitive emotion regulation in mothers of children with cancer - Mohammad Saleh Ashena; Mohammad Ali Besharat; Saied Malihialzuckerini; zohreh rafezi (مجله علوم روانشناختی, 2021)
Background: Studies have shown that Unified transdiagnostic therapy is unique in this emphasis on how to experience and respond to emotions. However, there is not any research on the effectiveness of Unified transdiagnostic therapy on the  Cognitive Emotion Regulation in mothers of children with cancer so far. Aims: The purpose of this study was to determine the effectiveness of Unified transdiagnostic therapy on Cognitive Emotion Regulation in mothers of children with cancer. Methods: This research was a quasi-experimental study with pre-test and post-test with the control group. The statistical population consisted of all mothers of children with cancer who were referred to Mahak, Shohada Tajrish, Bahrami, Hazrate Ali Asghar hospitals, in 2019 in Tehran. 31 mothers were selected by available sampling method and randomly assigned to 15 cases in the experimental group and 16 cases in the control group. The present research tools are the Cognitive Emotion Regulation Questionnaire (CERQ) short form (Garnefski & Kraaij,2006) and Unified Transdiagnostic Therapy (Barlow, 2011). The experimental group received the Unified Transdiagnostic Therapy for 12 sessions, each for 90 minutes. Data analysis was performed by the univariate analysis of covariance analysis method and using SPSS23 software. Results: The results showed Unified transdiagnostic therapy in the experimental group has increased using adaptive strategies compared to the control group include acceptance, positive refocusing, refocus on planning, positive reappraisal, and putting into perspective and also, it has led to a significant reduction in using maladaptive strategies include, self-blame, rumination, catastrophizing, and other-blame (P≤ 0.001). Conclusion: Unified transdiagnostic therapy increases using adaptive strategies and decreases using maladaptive strategies in mothers of children with cancer that this process will help improve the mental health of these mothers.